Nanomaterials and the interface between nanotechnology and environment - Peter A Schulz (Fundação Oswaldo Cruz (FIOCRUZ), 2013)
Nanomaterials are the main products of nanotechnology. In this paper we describe some of these nanomaterials, particularly Carbon based systems, their properties, manipulation strategies and applications. History of nanoparticles, as well as the comple-xity in defining nanomaterials, necessary for regulation and assessment of impacts on society, are also addressed.